Sudden Ocular Complication after Snake Bite: Poster Presentation - Case Report - General practitioner - Hadrani, Farah Hayati; Oktaputri, Anita; Widodo, Galih; Susetio, Yoseph (Majalah Oftalmologi Indonesia, 2023)
Introduction : A snakebite constitutes a common acute medical emergency and has several systemic and even ocular consequences. Snake venom neurotoxins act mainly on the peripheral nervous system at the neuromuscular junction and can affect the cranial nerves. Neurological symptoms that relate to cephalic muscle paralysis include exotropia, ptosis, diplopia and ophthalmoplegia. Case Illustration : A 17 years old man came to emergency department with painful swelling on his left hand and sudden blurred vision right after his left hand were bitten by venomous snake in the rice field. Diplopia and ptosis were developed several hours after admission. On eye examination, visual acuity was 0,05 on right eye and 0,8 on left eye, abnormal pupillary reflects on both eyes were present, pupil dilatation, limited eye movement and ptosis were present, Intraocular pressure were 23,7 mmHg on right eye and 24,5 mmHg on left eye. Antivenom was administered immediately. He received cycloplegic, timolol eyedrop, and prednisolone eyedrop for ocular treatment Discussion : Ocular complications are rare and uncommon but they may lead to sight-threatening conditions. Snake venom neurotoxins act mainly on the peripheral nervous system at the neuromuscular junction and can affect the cranial nerves. Mild neurological symptoms that relate to cephalic muscle paralysis include exotropia, ptosis, diplopia and ophthalmoplegia. Conclusion : This study presented a rare case of systemic ocular complication as a result of a snake bite. Ophthalmoplegia induced ocular discomfort for an extended period is a rare symptom of snake-bites. Combined treatment of steroid with antivenom may improve the recovery from sudden ocular manifestation in snake bite.